The Effect of Leadership Style and Work Motivation on Employee Performance at PT. Barito Oakwood Retailindo South Jakarta - Mulyani, Sri; Seta, Anggada Bayu; Gandung, Muhammad; Suwanto, Suwanto; Yuangga, Kharisma Danang (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The purpose of this study is to determine the influence of Leadership Style and Work Motivation on Employee Performance at PT Barito Oakwood Retailind, South Jakarta. The method used is a causal associative method using quantitative. The sampling technique used is saturated sampling using a sample of 60 respondents. The results of this study are that Leadership Style has a significant effect on Employee Performance with a correlation coefficient of 0.512 having a moderate level of relationship. Hypothesis testing obtained tcount > ttable or (4.541 > 2.002) thus H0 is rejected and H1 is accepted meaning that there is a partial effect between Leadership Style on Employee Performance at PT Barito Oakwood Retailindo South Jakarta. Work Motivation has an effect on Employee Performance at PT Barito Oakwood Retailindo with a correlation coefficient of 0.658 having a strong relationship level. Hypothesis testing obtained tcount > ttable or (6.661 > 2.002) thus H0 is rejected and H1 is accepted meaning that there is a partial significant effect between Work Motivation on Employee Performance at PT Barito Oakwood Retailndo, South Jakarta. Leadership Style and Work Motivation have an effect on Employee Performance at PT Barito Oakwood Retailindo South Jakarta with a correlation coefficient of 0.750 having a strong relationship level. Hypothesis testing obtained Fcount > Ftable or (36.629 > 3.16) thus H0 is rejected and H1 is accepted meaning that there is a simultaneous influence between Leadership Style and Work Motivation on Employee Performance at PT Barito Oakwood Retailindo South Jakarta.